Influence of the Ionic Liquid Cosolvent on Glucosylation Reactions Catalyzed by b-Glycosidase for Production of Salidroside - Bi, Yanhong; Zhu, Chun; Wang, Zhaoyu; Jia, Jianbo (Asian Journal of Chemistry, 2013)
The enzymatic synthesis of salidroside catalyzed by b-glycosidase from Malus pumila seed meal has been successfully carried out in ionic liquids-containing systems for the first time. The optimum conditions were screened out and the best yield of 24.9 % was received in the C4MIm·PF6-containing cosolvent system. Moreover, the influence of ionic liquids on the performance of the enzyme has been discussed, using both hydrophobic and hydrophilic ionic liquids possessing various anions and different alkyl chain lengths (C2-C10) in imidazolium cations.